2016
DOI: 10.3109/10641963.2015.1116546
|View full text |Cite
|
Sign up to set email alerts
|

Stress and hypertensive disease: adrenals as a link. Experimental study on hypertensive ISIAH rat strain

Abstract: ISIAH rats may serve as a living proof that stress may produce sustained hypertension, and genetically determined enhanced stress responsiveness of corticosterone and, especially, aldosterone may play a crucial role in the mechanism of hypertension development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 49 publications
1
9
0
1
Order By: Relevance
“…Our previous studies confirmed the reduced activity of 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) in adrenal glands of ISIAH rats [21] and in peripheral blood plasma [10]. It was shown that the loss-of-function mutations or inhibition of 11β-HSD2 results in overstimulation of the mineralocorticoid receptor by glucocorticoids and causes salt-sensitive hypertension [22].…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations
“…Our previous studies confirmed the reduced activity of 11β-hydroxysteroid dehydrogenase type 2 (11β-HSD2) in adrenal glands of ISIAH rats [21] and in peripheral blood plasma [10]. It was shown that the loss-of-function mutations or inhibition of 11β-HSD2 results in overstimulation of the mineralocorticoid receptor by glucocorticoids and causes salt-sensitive hypertension [22].…”
Section: Discussionsupporting
confidence: 74%
“…The peripheral plasma aldosterone concentration and secretion rates of corticosterone, 11-dehydrocorticosterone and deoxycorticosterone measured by the adrenal vein cannulation were significantly higher in the ISIAH rats as compared to control WAG rats [10]. The sympathetic adrenal medullary function assessed by measurement of the adrenal catecholamine content showed decreased concentrations of dopamine and norepinephrine, but significantly enhanced level of epinephrine in the adrenals of ISIAH rats [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the reduction in glomerular number is also associated with hypertension representing a vicious cycle where both the loss of glomeruli induces hypertension and hypertension promotes glomerular loss [11,24,25]. On the other hand, under stressful conditions, the hypothalamicpituitary-adrenal axis is further activated; recently, it has been demonstrated that a dominance of this axis over the renin-angiotensin-aldosterone system induce hypertension [26,27]. This reinforces the importance of reducing stress during any phase of life.…”
Section: Discussionmentioning
confidence: 86%